1992
DOI: 10.1148/radiology.182.3.1311119
|View full text |Cite
|
Sign up to set email alerts
|

Liver tumors: follow-up with P-31 MR spectroscopy after local chemotherapy and chemoembolization.

Abstract: The authors examined and quantified the changes observed in the phosphorus-31 magnetic resonance (MR) spectra of liver tumors after chemotherapy and chemoembolization to investigate the suitability of P-31 MR spectroscopy for follow-up. A 1.5-T unit was used before and at specific times during therapy to obtain spectra of liver tumors in 10 patients with liver metastases from colorectal carcinoma and two patients with hepatocellular carcinoma. A marked increase in inorganic phosphate and a decrease in the alph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1

Year Published

1992
1992
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 0 publications
1
31
1
Order By: Relevance
“…'~' Hyperthermia with intraarterial chemotherapy induced necrotic changes in a melan~ma.~' Chemoembolization caused necrotic changes in liver cancer^^*^^*'^ and in one study a marked early increase in Pi in all 10 responding cancers but no change in the 31P MRS in the 2 non-responders. 166 Intravenous chemotherapy with a nitrosourea caused an early decrease in pH in gliomas, although intra-arterial injection caused an early increase in P H . ~ The role of oxygenation in radiosensitivity is well established in experimental systems and there is some evidence for its role in human cancers although it is only one of several important f a~t 0 r s .…”
Section: Ischemia Hypoxia and Necrosis In Human Cancersmentioning
confidence: 99%
“…'~' Hyperthermia with intraarterial chemotherapy induced necrotic changes in a melan~ma.~' Chemoembolization caused necrotic changes in liver cancer^^*^^*'^ and in one study a marked early increase in Pi in all 10 responding cancers but no change in the 31P MRS in the 2 non-responders. 166 Intravenous chemotherapy with a nitrosourea caused an early decrease in pH in gliomas, although intra-arterial injection caused an early increase in P H . ~ The role of oxygenation in radiosensitivity is well established in experimental systems and there is some evidence for its role in human cancers although it is only one of several important f a~t 0 r s .…”
Section: Ischemia Hypoxia and Necrosis In Human Cancersmentioning
confidence: 99%
“…MRS has also been used to evaluate the prostate (14), breast (15, 16), and uterine cervix (17), as well as to evaluate diffuse hepatic disease, such as hepatic steatosis (18), chronic hepatitis (19, 20), and cirrhosis (21, 22). Phosphorus‐31 MRS has been used to assess hepatocellular adenomas (23), a variety of hepatic tumors (24, 25), and for the assessment of the effect of chemoembolization treatment (26). However, in the previous studies, in order to get enough signal‐to‐noise ratios for subsequent spectral analysis, the areas of interest were limited to peripheral locations and close to receiver surface coils.…”
mentioning
confidence: 99%
“…9 In another study of 22 patients with lymphomas, a decrease in PME was shown in all but one of the patients who had abnormally high ratios of PME/ATP in their initial spectra. 10 This change was seen as early as one day and as late as two weeks after commencing treatment.…”
Section: P Study Of Human Hepatic Tumoursmentioning
confidence: 92%